Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams Unemployment [Picture] 1899 [Picture] 1908 [Picture] 1916 [Picture] 1921 [Picture] 1927 [Picture] 1932 [Picture] 1942 [Picture] Each symbol represents 1% unemployed among members of British Trade Unions or insured workers 15X/2/566/303